Nově objevený rukopis Boženy Čapkové - Thořová, Věra (Lidé města, 2009)
An edition of three tales and seven legendary stories from the Úpice region, that Božena Čapková (1866 – 1924) collected over one hundred years ago and that was lost in the estates of Čeněk Zíbrt.